Utilization of Cinnamon Leaf and Shrimp Flour as an Enhancer of Catfish Meat Quality - Mia Setiawati; Suclyadi Dairun; Muhammad Agus Suprayudi; Nur Bambang Priyo Utomo (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Catfish (Pangasianodon hypophthalmus) is a freshwater fish that has been produced in the form of a filet. One of the problems in producing good catfish fillet is compactness and brightness of catfish farmed meat. This research aimed to get feed formulation as enhancer meat quality of striped catfish with added Cinnamon leaves flour (Cinnamomum burmannii) and used shrimp head meal. A Fish with a weight of 208.98±25.76 g reared in 12 floating nets cage (2x1x1.5 m3) with density of 15 fish/nets for 60 days. As treatment, fish were fed with feed contains 1% cinnamon leaves, 45% shrimp head meal, and combined of cinnamon leaves and shrimp head meal, and as control used feed were formulated without cinnamon leaves and shrimp head meal. Fish were fed 2 times a daily with feeding rate 3.5% of average body weight offish. The test parameters observed were physical, chemical and organoleptic test of catfish meat. The results showed feed with contains cinnamon leaves and shrimp head meal could decrease level of body fat 14.7% compared than control (p<0.05). Feed with used cinnamon leaves and shrimp head meal gave a texture offillet fish more compact, elastic and color of fillet fish white.